On the meaning and measurement of redistribution in cross-country comparisons - Peter J. Lambert; Runa Nesbakken; Thor O. Thoresen (Statistics Norway, Research Department, 2011)
Empirical findings on the relationship between income inequality and redistribution from a cross-country perspective are not conclusive. One reason may be that observers have in mind different concepts of redistribution. A major factor is that comparator countries' pre-fisc distributions typically differ markedly, and account is taken of this differently (if at all) by different measures of redistribution. The ambiguities can be resolved by applying the "transplant-and-compare" approach, rendering fiscal regimes into a common base by adjusting for differences in pre-fisc income inequality, and then measuring the "pure" effect of tax-and-transfer policies using this benchmark. We illustrate both what is possible, and what remains problematic, using this technique, by conducting an exploratory international comparison, based on microdata from the Luxembourg Income Study database in combination with more aggregated information from the OECD, for 15 countries.
Keywords: H11; H23; H53; 330; Redistributive effect; Personal income tax; Cross-country comparison